Pemilihan Langsung Presiden dan Wakil Presiden - Jimly Asshiddiqie (Universitas Islam Indonesia, 2004)
People aspiration soon after the collapse of Soeharto in 1998has lead to the constitutional reformation. -4s has been clearly understood, The 1945 Constitution, then has been amanded four times during very short period (from 1999-2002); a change which is never happen in any country worldwide. Presidential election mechanism is one of the most important aspects in such amandement in the near coming election, the president will be choosen directly by people. But, what people should understand about direct presidential election is that this is not only a chance to get better president who is trusted by all people, but also the mechanism of election will perform as the way to run costitutional system as has been agreed stated in in the amanded constitution.